Experimental studies on seismic performance of three‐storey steel moment resisting frame model with scissor‐jack‐magnetorheological damper energy dissipation systems. Issue 5 (18th September 2013) - Rama Raju, K.; Jame, A.; Gopalakrishnan, N.; Muthumani, K.; Iyer, Nagesh R.
SUMMARY The supplemental passive and semi‐active dampers such as viscous fluid dampers, magnetorheological (MR) dampers are increasingly used to provide enhanced seismic protection of structures. A three‐storey quarter length scale steel moment resisting frame (SMRF) model, fitted with two scissor‐jack‐MR damper systems placed at ground floor level, is designed and fabricated to study its seismic response characteristics. The effective damping of the frame model for different input currents to MR dampers are found using half power bandwidth method. The effective damping ratio is found to be maximum at 0A input current to MR dampers, and it is decreasing with the increase in input current to dampers. The natural frequencies of the model with MR dampers at different input currents are found. It is observed that the natural frequency of the model increases with increase in input current to MR dampers. The model is subjected to two types of near field and two types of far field seismic excitations. From the observation of responses, it is noted that the variation of reductions in displacements and inter‐storey drifts in the frame model beyond 0A input current to MR dampers are not significant. For all four excitations, the storey shears of the model are decreasing at 0A input current to MR dampers. The storey shears of the model are found to be increasing with increase in input currents in MR dampers beyond 0A. From experimental studies, it has been demonstrated that the scissor‐jack‐MR damper systems are effective in improving the performance of the building. Copyright © 2013 John Wiley & Sons, Ltd.